Genetic structure of the white‐footed mouse in the context of the emergence of Lyme disease in southern Québec. Issue 7 (3rd June 2013) - Rogic, Anita; Tessier, Nathalie; Legendre, Pierre; Lapointe, François‐Joseph; Millien, Virginie
Abstract: The white‐footed mouse ( Peromyscus leucopus ) has expanded its northern limit into southern Québec over the last few decades. P. leucopus is a great disperser and colonizer and is of particular interest because it is considered a primary reservoir for the spirochete bacterium that causes Lyme disease. There is no current information on the gene flow between mouse populations on the mountains and forest fragments found scattered throughout the Montérégie region in southern Québec, and whether various landscape barriers have an effect on their dispersal. We conducted a population genetics analysis on eleven P. leucopus populations using eleven microsatellite markers and showed that isolation by distance was weak, yet barriers were effective. The agricultural matrix had the least effect on gene flow, whereas highways and main rivers were effective barriers. The abundance of ticks collected from mice varied within the study area. Both ticks and mice were screened for the presence of the spirochete bacterium Borrelia burgdorferi, and we predicted areas of greater risk for Lyme disease. Merging our results with ongoing Lyme disease surveillance programs will help determine the future threat of this disease in Québec, and will contribute toward disease prevention and management strategies throughout fragmented landscapes in southern Canada. Abstract : The white‐footed mouse is primary reservoir for Lyme disease, and is expanding into Quebec. The genetic structure of 11 populations of the mouse from a fragmented landscape in Southern Quebec is affected by geographic barriers such as rivers and roads, which impacts the spatial distribution of Lyme disease in the area.